Total Demand Curves–A Reply - Pearce, I. F. (Review of Economic Studies, 1955)
Journal Article Total Demand Curves — A Reply Get access I. F. Pearce I. F. Pearce Nottingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 153–162, https://doi.org/10.2307/2296299 Published: 01 January 1955